2019
DOI: 10.1021/acs.joc.8b01411
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and O-Glycosidic Linkage Conformational Analysis of 13C-Labeled Oligosaccharide Fragments of an Antifreeze Glycolipid

Abstract: NMR studies of two 13C-labeled disaccharides and a tetrasaccharide were undertaken that comprise the backbone of a novel thermal hysteresis glycolipid containing a linear glycan sequence of alternating [βXylp-(1→4)-βManp-(1→4)] n dimers. Experimental trans-glycoside NMR J-couplings, parameterized equations obtained from density functional theory (DFT) calculations, and an in-house circular statistics package (MA’AT) were used to derive conformational models of linkage torsion angles ϕ and ψ in solution, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 69 publications
3
33
0
Order By: Relevance
“…Similar observations were made recently in similar comparisons of NMR-and MD-determined behaviors of ϕ in β-(1→4) linkages. 15,71 In contrast to ϕ, mean values of ψ obtained by MD simulation compare favorably with values determined from MA'AT analysis (Table S11; Supporting Information). For example, mean values of ψ for the αMan-(1→2)-αMan linkages in 2 and 7 were found by MD to be 21°and 22°, respectively, compared to 20.2°and 19.5°, respectively, by NMR J-coupling analysis.…”
Section: Parameterization Of J-coupling Equations For α-(1→mentioning
confidence: 69%
See 1 more Smart Citation
“…Similar observations were made recently in similar comparisons of NMR-and MD-determined behaviors of ϕ in β-(1→4) linkages. 15,71 In contrast to ϕ, mean values of ψ obtained by MD simulation compare favorably with values determined from MA'AT analysis (Table S11; Supporting Information). For example, mean values of ψ for the αMan-(1→2)-αMan linkages in 2 and 7 were found by MD to be 21°and 22°, respectively, compared to 20.2°and 19.5°, respectively, by NMR J-coupling analysis.…”
Section: Parameterization Of J-coupling Equations For α-(1→mentioning
confidence: 69%
“…Additional J -coupling constraints may also improve the modeling; for example, for the αMan-(1→3)-α/βMan linkage, 2 J H1′,C2′ may serve as an additional constraint on ϕ, while 2 J C2,H3 , 2 J C4,H3 , and 2 J C2,C4 may serve as constraints on ψ (Scheme ). , …”
Section: Resultsmentioning
confidence: 99%
“…However, generating a 3D structure solely from NMR data is rather difficult. The combination of NMR experiments with theoretical MD simulations is often employed and provided important structural information …”
Section: Methods To Study Polysaccharide Conformations and Foldingmentioning
confidence: 99%
“…Very recently, Lin, et al [376] prepared and studied by the solid-state 13 C NMR spectroscopy and DFT calculations seven doubly 13 In this direction, NMR studies of 13 C-labeled disaccharides 98-101 and a tetrasaccharide 102 shown in Scheme 17 were undertaken. [377] The experimental transglycoside NMR 1 H-1 H spin-spin coupling constants together with the related parameterized equations obtained from the related DFT calculations were used to derive conformational models of linkage torsion angles in solution, which were compared to those obtained from the molecular dynamics simulations.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Reproduced with minor editing privilege from Lin, et al [376] with the permission of the Royal Society of Chemistry (102). Reproduced with minor editing privilege from Zhang, et al [377] with the permission of the American Chemical Society…”
Section: Bioorganic Compoundsmentioning
confidence: 99%